Strength and Conditioning for Sports Performance - Jeffreys, Ian; Moody, Jeremy (Routledge, 2021)
"An effective strength and conditioning program is an essential component of the preparation of any athlete or sportsperson. Strength and Conditioning for Sports Performance is a comprehensive and authoritative introduction to the theory and practice of strength and conditioning, providing students, coaches and athletes with everything they need to design and implement effective training programs. Revised and updated for a second edition, the book continues to include clear and rigorous explanations of the core science underpinning strength and conditioning techniques and give detailed, step-by-step guides to all key training methodologies, including training for strength, speed, endurance, flexibility and plyometrics. The second edition expends on the opening coaching section as well as introducing an entirely new section on current training methods which includes examining skill acquisition and motor learning. Throughout the book the focus is on the coaching process, with every chapter highlighting the application of strength and conditioning techniques in everyday coaching situations. Strength and Conditioning for Sports Performance includes a unique and extensive section of sport-specific chapters, each of which examines in detail the application of strength and conditioning to a particular sport, from soccer and basketball to golf and track and field athletics. The second edition sees this section expended to include other such sports as rugby union, rugby league, American football, and more. The book includes contributions from world-leading strength and conditioning specialists including coaches who have worked with Olympic gold medallists and international sports teams at the highest level. Strength and Conditioning for Sports Performance is an essential course text for any degree level student with an interest in strength and conditioning, for all students looking to achieve professional accreditation, and an invaluable reference for all practising strength and conditioning coaches"--